HEMISOLEUS MUSCLE FLAP, A BETTER OPTION FOR COVERAGE OF OPEN FRACTURES INVOLVING MIDDLE THIRD OF TIBIA - Haq, Ata -ul-; Tarar, Moazzam Nazeer; Malik, Falak Sher; Khalid, Kamran; Riaz, Ahsan; Mehrose, Mohammad Younas; Khan, Husnain (Journal of Ayub Medical College Abbottabad, 2009)
Background: Local reconstructive options for middle third of leg make good use of Soleus muscle flap. Soleus being the prime ankle planter flexor and stabiliser of the ankle in ambulation cannot be sacrificed without significant morbidity. Soleus is a bipennate muscle with independent blood supply of each half. Using one half retains its important function, increases arc of rotation, and makes it easy to orientate for coverage of defect of any shape thus obviating the need for use of whole Soleus muscle flap. Due to this geometrical advantage, it is a superior option than the whole Soleus. We conducted a study to evaluate the reliability of the medial hemisoleus muscle flap for coverage of middle third tibial defects. Methods: This descriptive study was conducted at department of plastic surgery, Jinnah Hospital, Lahore from August 2008 to May 2009. Ten patients with middle third tibial defects were included in the study. All the patients were provided soft tissue coverage with proximally based medial hemisoleus muscle flap with split thickness skin graft on it. Results: All the flaps survived with primary healing of the wound except one patient who developed wound infection which settled after wound drainage and irrigation. Conclusion: Hemisoleus muscle flap is a valuable local option for soft tissue coverage of middle third of lower leg. It does not sacrifice the whole function of the Soleus muscle. Due to its longer arc of rotation, this flap can cover the defects of different size and shape in middle third of leg. Keywords: Hemisoleus muscle flap, soft tissue coverage, lower extremity reconstruction.